ANALISIS GANGGUAN KEAMANAN DAN PROTEKSI PADA ASUHAN KEPERAWATAN TN. H DENGAN DIAGNOSA MEDIS CEDERA KEPALA RINGAN (CKR) DI RUANG ANTASENA RST WIJAYAKUSUMA PURWOKERTO - Debi Ari Setiawan; Desy Dwi Kustiyanti; Made Suandika (Bajang Institute, 2022)
Head injury is a traumatic disorder of brain function. Complications of head injury are infection and bleeding. Trauma caused by wounds can be fatal and prevention of the risk of infection needs to be done. Implementing proper wound care procedures will accelerate wound healing. Honey can be used in various modern medicine because it has a therapeutic effect. This study used a descriptive design in the form of a case study approach to nursing practice. The case study in this study examined the risk of infection related to skin and tissue integrity of patients with mild head injury (CKR) after effective wound care using honey for 3 x 24 hours. The results showed that the problems that occurred in the client could be resolved on the 3rd day and which was marked by the patient's wound looking cleaner, there was no redness, there was no minimal bleeding. The patient looks cooperative during the wound care process, the patient seems to be able to get up or sit in bed, the tissue damage decreased on a scale of 4, the damage to the skin layer decreased on a scale of 4, redness decreased on a scale of 4 and bleeding decreased on a scale of 5. Nursing actions by performing wound care using honey can improve skin and tissue integrity which needs to be done in patients at risk of infection due to impaired skin and tissue integrity.